The Influence of Perception and Service Quality on Customer Satisfaction at Swiss-Belhotel in Ambon City - Rahmatia, Rahmatia; Wairisal, Paulus Liberthy; Sinay, Francisca Riconita (JENDELA PENGETAHUAN, 2025)
This study aims to analyze the effect of perception and service quality on customer satisfaction at the Swiss Hotel Ambon. Perception and service quality are two essential factors that influence the overall customer experience during their stay. The research employs a quantitative method with a descriptive approach, collecting data through questionnaires from 50 respondents who are guests of the Swiss Hotel Ambon. Data analysis was performed using SPSS to test validity, reliability, and multiple linear regression analysis. The findings indicate that both perception and service quality have a positive and significant effect on customer satisfaction, both partially and simultaneously. The coefficient of determination (R²) value of 0.892 suggests that 89.2% of the variance in customer satisfaction can be explained by these two variables. In conclusion, the hotel must maintain and enhance customer perceptions and service quality to ensure high customer satisfaction, which can contribute to customer loyalty and a positive reputation in the competitive hospitality market